High-performance sports and women's health in cyclical sports - Kogan, O. S.; Galiullina, S. D.; Yamilyova, R. M.; Greb, A. V. (Theory and Practice of Physical Culture, 2025)
Objective of studywas to explore the healthstatus of women in cyclical sports (short and long-distance running, cross-country skiing, speed skating, swimming),highly qualified athletes -"master of sports"and"master of sports of international class", who regularly participate in competitions in the Republic of Bashkortostan and Russia and have no income other than wages as a member of a sportsclub, a scholarship from the Federal Agency for Physical Culture and Sports of the Russian Federation or the Ministry of Physical Culture and Sports of the Republic of Bashkortostan.